The Role of Corruption, FDI, and Unemployment in ASEAN-5 Economic Growth - Husna, Putri Amalia; Nasir, Muhammad (Grimsa Journal of Business and Economics Studies, 2024)
Corruption is a global issue that remains unresolved to this day. It can lead to a decrease in investment and inefficiency in government spending allocation, impacting economic growth. Therefore, controlling corruption is a crucial issue that cannot be underestimated. This study uses panel data from 2012 to 2022 in ASEAN-5 countries (Indonesia, Malaysia, Vietnam, Laos, and Thailand). The method used is panel data regression with a fixed-effect model (FEM). The results indicate that foreign direct investment (FDI) has a significant positive effect on economic growth, while the corruption perception index and unemployment have no significant impact in the ASEAN-5 countries. This study suggests that promoting FDI is key to ASEAN-5's economic growth. Additionally, addressing corruption and unemployment through governance and labor market reforms is also crucial for sustainable development in the region.